Conference proceedings / XIII. International Conference on Logistics in Agriculture 2019, [Novo mesto, Slovenia, 6. November 2019] (University of Maribor Press, 2019)
The 13th International Conference on Logistics in Agriculture, which has been organized by the Municipality of Sevnica, Grm Novo mesto - Biotechnology and Tourism Center, Faculty of Logistics, University of Maribor, Landscape Governance College GRM, Cooperative Union of Slovenia has this year’s central theme the role and importance of human resources in logistics in agriculture. The conference has become traditional and paves the way for a different view of logistics in connection with agriculture. That’s why we have invited lecturers on the topic Electric vehicles in agriculture.